2010
DOI: 10.1523/jneurosci.5221-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Disintegrin/Metalloproteinase ADAM10 Is Essential for the Establishment of the Brain Cortex

Abstract: The metalloproteinase and major amyloid precursor protein (APP) ␣-secretase candidate ADAM10 is responsible for the shedding of proteins important for brain development, such as cadherins, ephrins, and Notch receptors. Adam10 ؊/؊ mice die at embryonic day 9.5, due to major defects in development of somites and vasculogenesis. To investigate the function of ADAM10 in brain, we generated Adam10 conditional knock-out (cKO) mice using a Nestin-Cre promotor, limiting ADAM10 inactivation to neural progenitor cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
316
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(334 citation statements)
references
References 75 publications
14
316
0
4
Order By: Relevance
“…30 This assumption was confirmed by RNAi-mediated silencing of ADAM10 and by using conditional ADAM10 knockout mice. 24,32 These findings were extended by the present study, which revealed association of the 5-HT 4 R with ADAM10. The ability of 5-HT 4 R to physically interact with mature ADAM10 was not shared by other GPCRs known to stimulate sAPPα secretion upon stimulation by their respective agonists.…”
supporting
confidence: 82%
“…30 This assumption was confirmed by RNAi-mediated silencing of ADAM10 and by using conditional ADAM10 knockout mice. 24,32 These findings were extended by the present study, which revealed association of the 5-HT 4 R with ADAM10. The ability of 5-HT 4 R to physically interact with mature ADAM10 was not shared by other GPCRs known to stimulate sAPPα secretion upon stimulation by their respective agonists.…”
supporting
confidence: 82%
“…Genetic ablation of ADAMs in the nervous system causes a 1 day delay in the loss of responsiveness to Sema3A both in vitro and in vivo. The complete physiological significance of this delay remains unresolved, since Nestin-Cre ADAM10 cKOs die at birth 58 . Thus, full assessment of the delay's implications on the correct wiring of proprioceptive fibres awaits the generation of more specific conditional knockouts.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent studies have convincingly demonstrated that at least in the CNS Notch, APP and N-cadherin are ADAM10 specific substrates 22,43 . In line with these findings, we have demonstrated that the proteolytic processing of these three substrates, as well as that of L1-CAM, is altered in Sfrp1/2 null mice.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this interpretation, we showed that pharmacological inhibition of ADAM10 can rescue the enhanced cell proliferation of Sfrp1 -/-;Sfrp2 -/-neural retina. Furthermore, conditional inactivation of Adam10 in neural progenitor cells causes a depletion of early progenitors and a reduction of α-secretase-mediated processing of APP 22 , a phenotype opposite to that observed in Sfrp1/2 null retinas or in the cortex of Sfrp1 -/-embryos (I. Crespo, P. Bovolenta and P.…”
Section: Discussionmentioning
confidence: 99%